An Investment Framework for Nutrition in Uganda : Reducing Stunting and Other Forms of Child Malnutrition - Shekar, Meera; Hyder, Zia; Subandoro, Ali; Dayton Eberwein, Julia; Pereira, Audrey; Akuoku, Jonathan Kweku (World Bank, Washington, DC, 2017)
This paper builds on global experience and Uganda's specific context to estimate costs,benefits, and cost-effectiveness of key nutrition interventions. It is intended to help guide theselection of the most cost-effective interventions as well as strategies for scaling these up. Thepaper considers both relevant "nutrition-specific" interventions, largely delivered through thehealth sector, and multisectoral "nutrition-sensitive" interventions, delivered through other sectors such as agriculture, education, and water and sanitation. We estimate that the costs and benefits of implementing 10 nutrition-specific interventions in all regions of Uganda would require a yearly public investment of $68 million. The expected benefits are enormous: annually over 8,000 lives would be saved, while at least 375,000 DALYs and 8,700 cases of stunting among children under five would be averted. Economic productivity could potentially increase by $280 million annually over the productive lives of the beneficiaries, with an impressive internal rate of return of 18 percent. However, because it is unlikely that the Government of Uganda or its partners will be able to find the $68 million necessary to reach full coverage, we also consider scale-up scenarios based on considerations of their potential for impact, burden of stunting, resource requirements, and implementation capacity. The most cost-effective scenario considered would provide a subset of key interventions in regions with the highest rates of stunting and would cost between $19 and $60 million, depending on how many regions are covered. We then identify and cost five nutrition sensitive interventions relevant to Uganda for which there is both evidence of positive impact on nutrition outcomes and some cost information. These findings point to a powerful set of nutrition specific interventions and a candidate list of nutrition-sensitive approaches that represent a highly cost-effective approach to reducing child malnutrition in Uganda.